The illustrious extinct. The disappearance of António Aurélio da Costa Ferreira remembered one hundred years later (1922-2022) - Ferreira, Nuno Martins (2023)
On July 15, 2022, one hundred years have passed since the disappearance of António Aurélio da Costa Ferreira. The importance of the intervention he maintained in the educational field, but also in science, namely in medicine, justifies the dissemination of his work, but the truth is that this event went completely unnoticed in the academic environment dedicated to the history of education in Portugal. This article aims to rescue aspects of his life and work, one hundred years after his death. We deliberately start from the echoes of his early disappearance in the periodical press and in Parliament to remember, later, his political and scientific action, but also as a trainer of future teachers, at the Escola Normal Primária de Lisboa, in Benfica. Although information on this last dimension is scarce, his role as a specialist in the work around child development fits in and, no less important, his legacy is noted at the current Escola Superior de Educação de Lisboa, in the field of Special Education.